Association between physical fitness and mood in 60-year-old women - Zanini, Gabriel [UNESP]; do Amaral, Vanessa Teixeira [UNESP]; Ferndes, Bianca; Ngomane, Awassi Yuphiwa [UNESP]; Testa, Ademir; Verardi, Carlos Eduardo Lopes [UNESP]; Ciolac, Emmanuel Gomes [UNESP] (Federacion Espanola de Asociaciones de Docentes de Educacion Fisica (FEADEF), 2023)
Background: It is known that trained individuals have better psychological behavior than less trained individuals, thus, it is speculated that better conditioning would be linked to this phenomenon. This study sought to verify whether better levels of functional capacity are associated with better mood patterns. Methods: Seventy-nine postmenopausal women (age = 70.3 ± 7.1 years) were then divided in four groups according to quartiles of functional capacity. The Brunel mood states scale were used to assess mood state and profile. Functional capacity assessment included measurements of handgrip strength, flexibility (sit and reach test), lower-limb strength (5 sit-to-stand test), balance (timed-up and go [TUG] test), and walking performance (6 minutes walking test). Results: The results showed higher functional capacity values are not associated with a better mood profile, even when the values obtained are classified as good or above average within their reference values. Conclusion: It was concluded that there is no association between the best functional capacity condition with the best mood profile. Perhaps this association is possible, if individuals are included in physical exercise programs.
Asociación entre condición física y estado de ánimo en mujeres de 60 años
Keywords: Aging; Funcional capacity; Mood States; Psychological Behavior